(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the impact of financial support on improving the level of healthcare services in Libyan healthcare institutions by analyzing the relationship between the amount of funding allocated to the health sector and the quality of healthcare services provided to citizens. The importance of the study stems from the vital role of healthcare financing in providing medical supplies, developing healthcare infrastructure, and enhancing the performance of medical and administrative staff. The study adopted a descriptive-analytical approach through a review of relevant literature and previous studies. The findings revealed a positive relationship between financial support and the level of healthcare services, as adequate funding contributes to improving the quality of healthcare, increasing the efficiency of healthcare institutions, and enhancing patient satisfaction. The study also recommended increasing financial allocations to the Libyan health sector and improving monitoring mechanisms for healthcare expenditures to ensure the optimal use of financial resources.